THE OCCUPATION IN CANTAMARCA, CANTA - Farfán Lobatón, Carlos (2000)
Base on the passed excavations results of this area, the author aims to manifest some aspects that assume inca occupation dynamic in Cantamarca. Besides, this research is focus on determining the importance of degree that this establishments had while the incas were pursuing to control che population that lived at both margins of che Chillon valley river in a effective way.